HISTOPATHOLOGICAL CHANGES IN THE GASTROINTESTINAL TRACT OF LOCAL CHICKENS INFECTED WITH PARASITE Choanotaenia infundibulum - MUSHATTAT, SUKAYNA JABBAR; AL-SAEDI, MARWA RAHMAN MOHAMED; HABER, SHAYMAA HUSSEIN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The Aim: This work to study Histopathological Changes in the Gastrointestinal Tract of Local Chickens Infected with Parasite Choanotaenia infundibulum. Place and Duration of Study: Raillietina cesticillus samples were obtained from the veterinary hospital with the help of specialized doctors. Study Design: A total of ten domestic hens infected with Choanotaenia infundibulum were investigated between March and July 2021 at the veterinary facility in Najaf Province, Iraq Methodology: Pathologically, there was a visible enlargement of the bowel, whereas histologically, alterations were more subtle. Unmistakable signs include inflammation of the epithelial layer and an abundance of cellular infiltration. Chronic inflammation and cell fragmentation in the epithelium Results: Macular degeneration as a result of the presence of this causes the villi to become disintegrated, removing any trace of the epithelial cells that line the digestive tract's villi and glands. Conclusion: It is noted that there is a smashing of the tops of the villi, sloughing, smashing, and inflammation in the epithelial layer of a wall accompanied by a large infiltration of inflammatory cells, especially eosinophils